2017
DOI: 10.1017/wet.2017.68
|View full text |Cite
|
Sign up to set email alerts
|

Glufosinate plus Dicamba for Rescue Palmer Amaranth Control in XtendFlexTMCotton

Abstract: Cotton growers commonly use glufosinate-based programs to control glyphosate-resistant Palmer amaranth. Palmer amaranth must be small (≤7.5 cm) for consistent control by glufosinate, and growers often miss the optimum application timing. XtendFlex™cotton may provide growers a tool to control larger Palmer amaranth. Glufosinate, dicamba, and glufosinate plus dicamba were compared for Palmer amaranth control in a rescue situation. Herbicides were applied to 16- to 23-cm weeds (POST-1) followed by a second applic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 36 publications
1
19
0
Order By: Relevance
“…Regrowth of Palmer amaranth is often a major concern associated with glufosinate applications as glufosinate does not prevent weed regrowth [26,27]. All treatments in this study resulted in similar and significantly lower leaf biomass and area 14 DAIT as compared to the nontreated control (Table 7).…”
Section: Greenhouse Studymentioning
confidence: 76%
See 1 more Smart Citation
“…Regrowth of Palmer amaranth is often a major concern associated with glufosinate applications as glufosinate does not prevent weed regrowth [26,27]. All treatments in this study resulted in similar and significantly lower leaf biomass and area 14 DAIT as compared to the nontreated control (Table 7).…”
Section: Greenhouse Studymentioning
confidence: 76%
“…Under such circumstances, producers often seek out rescue herbicide programs to control large escapes and prevent crop loss [19,[21][22][23]. Combinations of glufosinate and synthetic auxins have been shown to be more effective on control of larger weeds than when applied alone [19,21,[24][25][26]. Merchant et al [24] observed up to 22%, 17%, and 11% greater Palmer amaranth control 20 d after application when glufosinate at 431 g ai ha −1 was tank mixed with 2,4-DB, 2,4-D, or dicamba than when these three herbicides applied alone at 1120, 1064, and 1120 g ai ha −1 , respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Among all weeds, Palmer amaranth had the greatest shift in importance in the Mid‐south from 1994/1995 to 2008/2009 advancing from 25th to 7th 18 . The rapid spread of Palmer amaranth populations resistant to glyphosate triggered extensive research for, and adoption of, new management strategies 19,20 . In Georgia, a 10‐fold increase in fomesafen and flumioxazin usage was reported after the spread of GR Palmer amaranth 21 .…”
Section: Introductionmentioning
confidence: 99%
“…The release of dicambaresistant genetically modified plants (soybean, cotton) by Monsanto is another important factor that promoted an increase worldwide use of dicamba. [3][4][5] However, dicamba from the old formulations was shown to drift after application. It was reported to vaporize from the treated fields and spread to neighboring non-resistant crops.…”
Section: Introductionmentioning
confidence: 99%